Prediabetes in adolescents- an emerging epidemic– a cross-sectional survey of medical students at a public university, Quetta, Pakistan - Faisal Shahzad; Aiesha Ishaque; Fahad Saleem (Journal of the Pakistan Medical Association, 2021)
Background and objectives: The prevalence of prediabetes is increasing globally affecting all age groups epically in adolescents. The objective of this study was to determine the prevalence and determinants of prediabetes in adolescent population studying in Public sector Medical University, Quetta, Pakistan. Methods: A cross-sectional study was conducted from December 2019 to February 2020. Students in their late adolescents (ages between 16 and 19 years) were enrolled in the study. Non-probability convenience sampling method was used. A self-administered questionnaire was administered to the students to collect socio-demographic data. Fasting blood sample was taken to measure the fasting blood glucose level, lipid profile and HbA1c. Height,weight, neck circumference and waist circumference were also measured. Statistical Package for Social Sciences SPSS v.21 was used to analyze data. Results: A total of 351 adolescent students were enrolled in the study, 158 (45%) were males and 193 (55%) were females. The overall mean age was 18.81±0.41 years. Based on being tested positive on both the glycemic parameters ie HbA1c and FBS 23.1% of our study participants were found to have prediabetes. Neck circumference was identified as the strongest predictor for prediabetes in our study. Other predictor variables included high TG, high SBP, low HDL, high LDL, high DBP, WC and BMI Conclusion: The prevalence of prediabetes is higher among male medical students. The NC, WC, BMI, SBP, DBP, TG and HDL were strong predictors of prediabetes in adolescent population. Continuous...